How would the expression x^{3} - 8 be rewritten using difference of cubes?

Thank you for the opportunity to help you with your question!

Use the formula of the differenceof cubes which is: a^3 - b^3 = (a - b)(a^2 + ab + b^2).

So we compare the given expression x^3 - 8 to the left side of the formula: a^3 - b^3.

Here, we can see: a^3 = x^3 and b^3 = 8. So we solve each equation by taking the cube root like this:

3th root(a^3) = 3th root(x^3) ---------> a = x

3th root(b^3) = 3th root(8) ------------> b = 2 (the cubic root of 8 is 2 since 2*2*2 = 8).

Then we enter x in place of a and 2 in place of b into the right side of the formula like this:

(a - b)(a^2 + ab + b^2) = (x - 2)(x^2 + 2x + 2^2) = (x - 2)(x^2 + 2x + 4) since 2^2 = 2*2 = 4.

So x^3 - 8 = (x - 2)(x^2 + 2x + 4).

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up